Mengajar dan Belajar Bahasa Inggris Menggunakan Google Classroom untuk Pelajar - Maulaniam Sholah, Hanif (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2020)
Technology takes all the integral roles in our life. Not only the roles of job commercial but also the roles of teaching and learning. Online learning is a typical teaching and learning process through electronic media of computers and the internet. This system calls an E-Learning or Blended Learning. E-Learning system is the manifest of Information and Communication Technology (ICT) that currently grows up rapidly in this modern era. In this 21st era, learners require to renew the knowledge of the way for learning through any technological tools. Both teachers and students must be aware of the use of technology and how to use it in the learning process. Some advantages of learning using ICT for teachers and students are necessary to be considered. Teachers can manage the large class efficiently because technology takes the teachers' role as the media of learning. Besides, a varied assignment can give effect. Then, the teacher can access the students' responses anytime in any places and also teachers can give feedback directly. Technology provides the chance of learning not only at school but also at home or in any place. This paper focuses on the understanding of using “Google Classroom" from the perspective of both teaching and learning. Findings in this research showed that Google Classroom could help teachers to manage the class, assignments, and report well. Students can learn any materials at any time and anywhere, track their progress, and students could enjoy learning like playing the game. This paper attempts to promote learning through online classes by joining www.googleclassroom.com, in which this online class is joyful for both teachers and students as Indonesian English learners. Keywords: Google Classroom, learning and teaching, online learning.